2004
DOI: 10.1074/jbc.m410619200
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mannose Limits the Growth of Phosphomannose Isomerase PMI40 Deletion Strain of Saccharomyces cerevisiae

Abstract: Phosphomannose isomerase (PMI40) catalyzes the conversion between fructose 6-phosphate and mannose 6-phosphate and thus connects glycolysis, i.e. energy production and GDP-mannose biosynthesis or cell wall synthesis in Saccharomyces cerevisiae. After PMI40 deletion (pmi ؊ ) the cells were viable only if fed with extracellular mannose and glucose. In an attempt to force the GDP-mannose synthesis in the pmi ؊ strain by increasing the extracellular mannose concentrations, the cells showed significantly reduced gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…3B), demonstrating that the glycolysis pathway could not rescue the growth of Mapmi-RNAi strain. Growth of mannose concentration-dependent Mapmi mutants was consistent with loss of cell function in Pmi deletion animal cells (DeRossi et al, 2006) and some fungal cells (Fang et al, 2009;Pitkänen et al, 2004;Wills et al, 2001). Biochemical analysis showed that M-6-P accumulated in pmi deletion mutants when exposed to excess mannose in S. cerevisiae (Pitkänen et al, 2004), while increased intracellular ATP occurred in Escherichia coli (de la Fuente et al, 1986).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…3B), demonstrating that the glycolysis pathway could not rescue the growth of Mapmi-RNAi strain. Growth of mannose concentration-dependent Mapmi mutants was consistent with loss of cell function in Pmi deletion animal cells (DeRossi et al, 2006) and some fungal cells (Fang et al, 2009;Pitkänen et al, 2004;Wills et al, 2001). Biochemical analysis showed that M-6-P accumulated in pmi deletion mutants when exposed to excess mannose in S. cerevisiae (Pitkänen et al, 2004), while increased intracellular ATP occurred in Escherichia coli (de la Fuente et al, 1986).…”
Section: Discussionmentioning
confidence: 68%
“…Mannose is involved also in the synthesis of the protective capsule and other structures within fungal cells (Bose et al, 2003;Fang et al, 2009;Pitkänen et al, 2004;Wills et al, 2001). GDP-mannose, a nucleotide sugar described by Cabib and Leloir (1954), has been demonstrated to be the activated donor of mannose for biosynthesis of mannose-containing glycoconjugates (Wills et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mannose and fructose are utilized according to the Kluyver rule (20), whereas glucose enters the glycolytic pathway directly. Using mannose as the sole carbon source inhibits the phosphomannose isomerase PMI40, which directs mannose into the glycolytic pathway (26); this constitutes another obstacle to the utilization of mannose for ethanol production.…”
Section: Discussionmentioning
confidence: 99%
“…The same approach can be used without replicates, providing that information from several arrays of the same type is available. As an example Figure 4 shows the result of comparing the yeast array GSM29929 (see Figure 2) with yeast arrays from two entirely unrelated experiments: GSM34758 from experiment GSE1938 (see Pitkänen et al (2004) for details) and GSM67551 from experiment GSE3076 (see Guan,et al (2006)). The flaws in GSM29929 that were very obvious in Figure 2 are still apparent (though they are much less apparent).…”
Section: Introductionómentioning
confidence: 98%